KEPEMIMPINAN ORANG TUA DALAM MEMBENTUK KARAKTER ANAK BERBASIS NILAI-NILAI AL-QUR’AN - Ahmad Shunhaji; Ahmad Zain Sarnoto; M. Imam Khudlori (STIT AL-AMIN KREO TANGERANG, 2022)
This research reveals the importance of forming children’s morals on the basis of the values of the Qur’an, for two reasons: 1) Doctrinal aspects: The Qur’an is a guidance for people in their lives, 2) Political aspects: Based on Law No. 20, Article 3 of 2003 regarding the national education system, it states that Education aims to make students devout believers. In the perspective of Islam, pious believers sought to practice the contents of the Qur'an and acquire morals based on the values of the Qur'an. The development of children's morals was influenced by parental education and parental leadership was a part of it. There are five ways for parents to form children's morals, which are: strict discipline; effective punishment; Participation in the use of non-print media (television, Internet); participation in the use of print media (books); exemplary (exemplary). There are four indicators of the foundation's formation on the values of the Qur'an, namely: absolute charity, general validity, obligatory responding (mandatory implementation), and the surrounding neck. This research was qualitative research based on data inference process on literature studies. The type of this research was desk research with a philosophical method to find out that the values of forming children's morals contained in the Qur'an can be applied to the operational field.